The Use Of Electronic Evidence In Civil Jurisdiction Processes In Indonesian Law Courts - Alfred Yetno Alfred; Ni Made Anggi Arlina Putri (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
In Law No. 11 of 2008 and Law No. 19 of 2016 on Electronic Information and Transactions, electronic evidence is an extension of legal evidence under the procedural law already applied in Indonesian courts to use it as legal evidence. Pre-trial and electronic evidence filing in court civil cases. The provision of electronic evidence is assessed by the arbitral tribunal based on whether the requirements for the form and material of electronic evidence are met, because there are no special procedural provisions for electronic evidence in the main court hearing, but there are further regulations on the form requirements of electronic evidence. It will be explained in Section 6 of the Act. Decree No. 11 of 2008 together with Law No. 19 of 2016 on Electronic Information and Transactions is considered valid as long as the information contained in it is accessible, viewable, guaranteed to be complete and interpretable to explain the situation. The substantive requirement of electronic evidence is the relevance of the evidence to the claim or disputed material. Therefore, the judge can regard electronic evidence as prima facie evidence, doubtful evidence, admission evidence, or it can be excluded or disregarded by the judge in accordance with No. 48 of 2009 on the powers of judges of the judiciary.